Emotional Development Questionnaire for Primary Education (CDE_9-13) - Núria Pérez-Escoda; Èlia López-Cassà; Alberto Alegre (MDPI AG, 2021)
This study presents the construction of the Emotional Development Questionnaire (CDE_9-13) and examines its psychometric properties. This questionnaire measures the emotional competence and its five dimensions-emotional awareness, emotional regulation, emotional autonomy, social competence, and life and well-being competence-of boys and girls from 9 to 13 years of age. Its construction followed the guidelines of the International Test Commission. The final version consists of 41 items. The total sample is 1905 boys and girls between the ages of 9 and 13, although partial samples have been used for specific analyses. Various studies have been carried out to demonstrate the reliability and validity of the instrument: the calculation of the reliability coefficient, a confirmatory factor analysis (CFA), and the correlational comparison of the CDE_9-13 with recognized measures of emotional intelligence, personality, adjustment difficulties, and self-esteem. Likewise, a regression study has been carried out to confirm the incremental validity. The CDE_9-13 is a theoretically well-founded questionnaire with appropriate psychometric characteristics. Therefore, it is considered an optimal tool to assess emotional competence in interventions aimed at promoting mental health and well-being.